2000
DOI: 10.1177/00220345000790120901
|View full text |Cite
|
Sign up to set email alerts
|

Detection of a Novel Mutation in X-linked Amelogenesis Imperfecta

Abstract: Amelogenesis imperfecta (AI) is a heterogeneous group of inherited disorders of defective enamel formation. The major protein involved in enamel formation, amelogenin, is encoded by a gene located at Xp22.1-Xp22.3. This study investigated the molecular defect producing a combined phenotype of hypoplasia and hypomineralization in a family with the clinical features and inheritance pattern of X-linked amelogenesis imperfecta (XAI). Genomic DNA was prepared from buccal cells sampled from family members. The DNA w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(33 citation statements)
references
References 17 publications
(12 reference statements)
0
31
0
1
Order By: Relevance
“…The genes responsible for AI in human patients include AMELX, AMBN, ENAM, MMP20, KLK4, WDR72, FAM83H, LAMB3, ITGB6, and SLC24A4 , and current evidence tends to support a single-gene origin for many AI cases (Aldred et al, 1992; Lench et al, 1994; Lagerstrom-Fermer and Landegren, 1995; Lagerstrom-Fermer et al, 1995; Collier et al, 1997; MacDougall et al, 1997; Hart et al, 2000, 2003, 2004, 2009; Kindelan et al, 2000; Mardh et al, 2002; Kim et al, 2004, 2005, 2008, 2013; El-Sayed et al, 2009; Wright et al, 2009; Poulter et al, 2014a,b,c; Wang S. et al, 2014; Wang S. K. et al, 2014; Herzog et al, 2015). Our data from the double-mutant animals ( Slc26a1 −/− / Slc26a7 −/− ) suggest that polygenic etiologic factors might also be involved in the pathogenesis of AI/AI-like symptoms, which increases the complexity of genetic diagnosis for enamel disorders.…”
Section: Discussionmentioning
confidence: 95%
“…The genes responsible for AI in human patients include AMELX, AMBN, ENAM, MMP20, KLK4, WDR72, FAM83H, LAMB3, ITGB6, and SLC24A4 , and current evidence tends to support a single-gene origin for many AI cases (Aldred et al, 1992; Lench et al, 1994; Lagerstrom-Fermer and Landegren, 1995; Lagerstrom-Fermer et al, 1995; Collier et al, 1997; MacDougall et al, 1997; Hart et al, 2000, 2003, 2004, 2009; Kindelan et al, 2000; Mardh et al, 2002; Kim et al, 2004, 2005, 2008, 2013; El-Sayed et al, 2009; Wright et al, 2009; Poulter et al, 2014a,b,c; Wang S. et al, 2014; Wang S. K. et al, 2014; Herzog et al, 2015). Our data from the double-mutant animals ( Slc26a1 −/− / Slc26a7 −/− ) suggest that polygenic etiologic factors might also be involved in the pathogenesis of AI/AI-like symptoms, which increases the complexity of genetic diagnosis for enamel disorders.…”
Section: Discussionmentioning
confidence: 95%
“…In humans, amelogenin genes are localized to the X (AMELX) and Y (AMELY) chromosomes. Mutational analyses have shown that X-linked AI (AIH1), a phenotypically diverse hereditary disorder aVecting enamel development, is caused by deletions or point mutations in human AMELX Kindelan et al 2000;Ravassipour et al 2000;Hart et al 2002;Kim et al 2004). Amelogenin-null mice displayed distinctly abnormal teeth with white, chalky discoloration, and the amelogenin-null phenotype revealed that amelogenins are essential for the organization of crystal pattern and regulation of enamel thickness (Gibson et al 2001; Bartlett et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Among all the enamel diseases, AI is the most severe inherited disorder, which inflicts great suffering and treatment cost on patients. To date, identified genes responsible for AI include AMELX, AMBN, ENAM, MMP20, KLK4, FAM83H and SLC24A4 ; however, it is estimated that mutations in these genes account for less than half of the documented cases of AI404142434445464748495051525354555657585960. Based on the present study, miR-153 overloading during enamel maturation induces significant hypomineralization—AI-like signs–in affected animal teeth (Fig.…”
Section: Discussionmentioning
confidence: 63%